Hubungan Aktivitas Fisik Dengan Demensia Pada Lansia Di Uptd Lanjut Usia Binjai Dinas Sosial Provinsi Sumatera Utara Tahun 2024 - Nurhayanti, Nurhayanti; Fadillah, Qori; Pratama, Irza Haicha (Syntax Corporation, 2025)
Dementia is one of the major health problems in the elderly, characterized by progressive cognitive decline that affects daily functioning and quality of life. Physical activity plays a protective role against dementia by increasing cerebral blood flow, improving neuronal function, and reducing cognitive degeneration. The Elderly Social Services Unit (UPTD Lanjut Usia) in Binjai accommodates elderly people with various characteristics, making it a representative setting to examine the relationship between physical activity and dementia. This study aimed to determine the association between physical activity and dementia among elderly residents of UPTD Lanjut Usia Binjai, North Sumatra Province, in 2024. This was an analytical quantitative study with a cross-sectional design. A total of 133 elderly respondents were included using total sampling. Physical activity levels were measured using the Physical Activity Scale for the Elderly (PASE), while cognitive status was assessed with the Mini-Mental State Examination (MMSE). Data analysis was performed using univariate methods for frequency distribution and bivariate analysis with the Spearman Rank test, with a significance level of p < 0.05. The findings showed that the majority of respondents had low physical activity levels (70.7%), while 21.1% had moderate activity and only 8.3% had high activity levels. Regarding cognitive status, 50.4% of respondents experienced definite dementia, 31.6% probable dementia, and only 18.0% remained cognitively normal. The Spearman Rank test revealed a significant association between physical activity and dementia (p = 0.000). There is a significant relationship between physical activity and dementia among the elderly at UPTD Lanjut Usia Binjai. Elderly individuals with lower levels of physical activity were more likely to experience dementia compared to those with moderate or high physical activity.